A Review Article: Advanced Concepts In The Prodrug Design (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Prodrugs are chemically improved compounds used in the treatment approach because of their valuable physicochemical characteristics (better stability, enhanced solubility, improved permeability) applied in an inactive form. The biological effect is applied by the active compounds obtained via chemical or enzymatic activation (biotransformation). About (10-15)% of drugs were designed as suitable prodrugs and about 50% were then transformed into active compounds through hydrolysis, mainly via ester hydrolysis. Prodrug Design aims to advance the compounds' bioavailability by overcoming unwanted features and lowering the first-pass metabolism. Also, other purposes include improvement of the compound absorption, prolongation of action duration or improvement of selectivity to the target. Types of prodrugs include Classic, Bioprecursors, Targeted, Mixed Prodrugs and Mutual Prodrugs.